2003
DOI: 10.1159/000076805
|View full text |Cite
|
Sign up to set email alerts
|

Flux of a Nickel(II) Salt versus a Nickel(II) Soap across Human Skin in vitro

Abstract: Background: Contrary to in vitro data on skin diffusivity of nickel salts indicating slow rates of diffusion, contact allergy to nickel among the general population is frequent, indicating facile skin penetration. Objective: To demonstrate that the preferred diffusion of a lipophilic oxidation product of nickel formed in contact with the skin follows the multilamellar lipid region which envelops the corneocytes. Method: Diffusion of nickel chloride was compared with that of the lipophilic nickel soap, the dioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Moody et al investigated in vitro dermal permeation of nickel as Ni-63 in soil and without soil by using human breast skin (refer to mercury for more detail) and found a high total absorption as a result of a high percentage of nickel retained inside the skin (depot/reservoir). Comparison of their results to those of Hostýnek indicated a lower percentage of permeation (1.8% vs. 35.7%) and a higher percentage of retention in the skin (20.9% vs. 0.02%). The authors suggested the appendageal shunt route as a contributing factor to the difference in results.…”
Section: Metalsmentioning
confidence: 87%
See 3 more Smart Citations
“…Moody et al investigated in vitro dermal permeation of nickel as Ni-63 in soil and without soil by using human breast skin (refer to mercury for more detail) and found a high total absorption as a result of a high percentage of nickel retained inside the skin (depot/reservoir). Comparison of their results to those of Hostýnek indicated a lower percentage of permeation (1.8% vs. 35.7%) and a higher percentage of retention in the skin (20.9% vs. 0.02%). The authors suggested the appendageal shunt route as a contributing factor to the difference in results.…”
Section: Metalsmentioning
confidence: 87%
“…The authors suggested that the higher permeability of NiCl 2 may be due to higher cutaneous bioavailability of the salt . Hostýnek , also reported higher permeability coefficients for NiCl 2 when compared with that of other nickel compounds. In contrast, Tanojo et al reported a higher percentage of permeation for NiSO 4 when compared with that of NiCl 2 when using the SC only.…”
Section: Metalsmentioning
confidence: 96%
See 2 more Smart Citations
“…10 In vitro methods using diffusion cells for assessment of percutaneous absorption, measure penetration of chemicals into the skin and their permeation into a receptor fluid. This methodology has been used with ex vivo human or piglet skin to study permeation of aqueous nickel chloride, nickel sulphate, [12][13][14] and pure nickel dissolved in HNO 3 . 15 Collectively, the studies show that nickel in different forms may penetrate into skin, even after short duration of exposure.…”
mentioning
confidence: 99%